Decreased excitability of leptin-sensitive anterior insula pyramidal neurons in a rat model of compulsive food demand. (1st May 2022) - Kirson, Dean; Spierling Bagsic, Samantha R.; Murphy, Jiayuan; Chang, Hang; Vlkolinsky, Roman; Pucci, Sarah N.; Prinzi, Julia; Williams, Casey A.; Fang, Savannah Y.; Roberto, Marisa; Zorrilla, Eric P.
Abstract: Compulsive eating is an overlapping construct with binge eating that shares many characteristics with substance use disorders. Compulsive eating may impact millions of Americans; presenting in some cases of binge eating disorders, overweight/obesity, and among individuals who have not yet been diagnosed with a recognized eating disorder. To study the behavioral and neurobiological underpinnings of compulsive eating, we employ a published rodent model using cyclic intermittent access to a palatable diet to develop a self-imposed binge-withdrawal cycle. Here, we further validated this model of compulsive eating in female Wistar rats, through the lens of behavioral economic analyses and observed heightened demand intensity, inelasticity and essential value as well as increased food-seeking during extinction. Using electrophysiological recordings in the anterior insular cortex, a region previously implicated in modulating compulsive-like eating in intermittent access models, we observed functional adaptations of pyramidal neurons. Within the same neurons, application of leptin led to further functional adaptations, suggesting a previously understudied, extrahypothalamic role of leptin in modulating feeding-related cortical circuits. Collectively, the findings suggest that leptin may modulate food-related motivation or decision-making via a plastic cortical circuit that is influenced by intermittent access to a preferred diet. These findings warrant further study of whether behavioral economics analysis of compulsive eating can impact disordered eating outcomes in humans and of the translational relevance of a leptin-sensitive anterior insular circuit implicated in these behaviors. Highlights: Intermittent access increased the essential value, demand intensity and inelasticity, and total work for a preferred food. Intermittent access led to adaptation of insula pyramidal neurons, with altered resistance, rheobase and spiking properties. The same medial, anterior insula region was shown to express functional leptin receptors by both qPCR and electrophysiology. Leptin reduced rheobase and increased spike amplitude of pyramidal neurons in INT rats, even if GABAB and iGluR were blocked.